Rehabilitasi Sekolah Dalam Mengatasi Masalah Siswa Di SMP Sabilul Muttaqin Tamberu Barat Sokobanah Sampang - Rahman, Zainur; Wahyudi, Achmad; Baidowi, Ach. (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2022)
School rehabilitation is an effort made by schools to overcome problems that exist in schools, including student problems. The purpose of this study was to describe the identification of problems and problem solving of students in Junior high school Sabilul Muttaqin Sampang. The research method is qualitative with an analytical study approach. Data collection techniques with interviews, observation and documentation. Data processing techniques with reduction, data presentation and conclusion. Technique of data validity by triangulation of sources and techniques. The results showed: (1) identification of student problems, including: discipline or activeness in school, school uniforms, student quantity, dislike of subject matter, dislike of teachers, bad ethical problems, and disobedience to school rules. (2) Handling student problems, among others: first with a face to face approach by giving directions and warnings to students. Second, giving awards to students who are disciplined and give punishment to students who are not disciplined (problematic).. The third is holding Muhadhoroh Bersama activities once a week. And fifth, providing guidance and counseling to students who have severe problems at school.